Desenvolvimento, produtividade e qualidade de infrutescência do abacaxizeiro ‘Imperial’ em função da adubação com N e K - Rios, Élica Santos (2017)
The cv. Imperial presents resistance to fusariose and has great commercial potential, because of characteristics such as flavor, aroma and color of the fruits. However, due to the need for diversification of cropping systems and the scarcity of information on a cv. Imperial, it is necessary to evaluate the effect of the fertilization and mineral nutrition of the pineapple on the production and quality of the fruits of the cv. Imperial. In this sense, this research was divided into three chapters. The first chapter aimed to evaluate the effect of fertilization with N and K on 'Imperial' pineapple on the growth and mineral nutrition of leaf D. In the second, the objective was to evaluate the vegetative growth of cv. Imperial fertilized with doses of N and K. And the third, had the objective to evaluate the productivity and physical-chemical characteristics of the infructescence of cv. Imperial, submitted to fertilization with N and K. The experiment was carried out in a randomized complete block design, with 10 treatments and three replications. The treatments were arranged according to the Plan Plueba III matrix, which consists of the combination of five doses of N (15; 90; 150; 210 and 285 kg ha-1) as urea and five doses of K (21,6; 129 , 6; 216.0; 302.4 and 410.4 kg ha-1) as KCl. In the first chapter, it was verified that the elevation of N doses increased linearly the median width of leaf D, SPAD index and leaf content of N. The application of K2O increased leaf D length, basal width, fresh and dry mass and leaf content of K2O. The relationship of nitrogen doses and days after planting presented linear and positive effects in relation to D leaf length, basal width and fresh and dry mass of leaf D. In the second chapter it was observed that the application of the higher doses of N (285 kg ha-1) and K2O (410 Kg ha-1) favored the vegetative growth of cv. Imperial, the total fresh mass production of the plant varied between 765.8 and 1.059.9 g plant-1 with application of 15 and 285 kg ha-1 of N, and ranged between 765 and 1,066.7 g plant-1 with 22 and 410 kg ha-1 of K2O, respectively. Nitrogen fertilization caused a 24.95% increase in total dry matter yield in relation to fertilization of 15 and 285 kg ha-1, respectively, at 375 days after planting. In the third chapter the results show that the elevation of the K2O doses linearly increased the weight of the fruit with crown, productivity, length and diameter of the fruit and the Soluble solids content. Crown yield decreased with x increasing doses of N and K2O. N rates increased the yield of the pulp, the a* and b* staining index of the peel and SS/AT. Increasing doses of N and K2O promote a positive effect on the physical-chemical characteristics of the fruits of the 'Imperial' pineapple. However, the doses used were not sufficient to obtain the maximum productive potential. The highest dose of K2O produced fruits weighing 632.34 g and yield of 26.36 t ha-1.